2009
DOI: 10.1002/ffj.1943
|View full text |Cite
|
Sign up to set email alerts
|

Liverwort Radula species from Portugal: chemotaxonomical evaluation of volatiles composition

Abstract: The volatiles isolated by distillation-extraction from 48 samples of seven liverwort Radula species collected on Azores and Madeira archipelagos and mainland Portugal, as well as one from Switzerland, were analysed by GC and GC-MS. Cluster analysis of the volatiles composition resulted in two major clusters. The chemically very diverse cluster I included the oil samples of Radula aquilegia from Madeira, R. jonesii, R. holtii, R. nudicaulis, R. lindenbergiana as well as R. complanata from Switzerland. Cluster I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The Madeira species was included in group I, whereas that from the Azores was in group II. [50] The studies also showed that the EOs from the specimens of the same Radula species where chemically very similar. This indicated chemotaxonomical value for the EO composition.…”
Section: Leafy Liverwortsmentioning
confidence: 88%
See 2 more Smart Citations
“…The Madeira species was included in group I, whereas that from the Azores was in group II. [50] The studies also showed that the EOs from the specimens of the same Radula species where chemically very similar. This indicated chemotaxonomical value for the EO composition.…”
Section: Leafy Liverwortsmentioning
confidence: 88%
“…Chemosystematic studies on the genus Radula growing in Portugal showed that on the basis of EO composition Radula species can be divided into two groups. [50] Group I was characterized by the presence of 3-methoxybibenzyl (44), β-bisabolene (45), (Z)-δ-bisabolene (46) and (E)-β-farnesene (47) in the EO and included the following species, R. holti, R. nudicaulis and R. lindenbergiana. This group also contained R. complanata collected in Switzerland.…”
Section: Leafy Liverwortsmentioning
confidence: 99%
See 1 more Smart Citation
“…158 The hepaticae have been the most studied due to the oil bodies specific to the class which allows more facile isolation of compounds into the organic extract. [97][98][99][100][101][102][156][157][158][159][160][161][162][163][164][165][166] Historically, these plants have been used for curing various ailments including bruises, burns, and even poisonous snake bites. 156 More than 400 years ago, the Chinese were even reported to have used these plants as diuretics and for hair growth.…”
Section: Chapter IV Synthesis Of Radulanins Through Organophopshorus mentioning
confidence: 99%
“…157,158,161 Liverwort extracts mainly consist of mono-, sesqui-, and diterpenoids, aromatics (including but not limited to bibenzyls, heterocycles, and long-chain alkyl phenols), and acetogenins ( Figure 41). [97][98][99][100][101][102][156][157][158][159][160][161][162][163][164][165][166] Interestingly, the sesqui-and diterpenoids isolated are often the enantiomers of compounds obtained from higher order plants. 156,157,159 Although very uncommon in liverworts, nitrogen-and sulfur-containing compounds have also been recently isolated from the species Corsinia coriandrina (163, Figure 41).…”
Section: Chapter IV Synthesis Of Radulanins Through Organophopshorus mentioning
confidence: 99%